2018
DOI: 10.3390/su10072115
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a Powerful Retailer on Dynamic Collecting Closed-Loop Supply Chain From a Sustainable Innovation Perspective

Abstract: In this study, the presence of a powerful retailer in the dynamic collecting closed-loop supply chain is considered. The supply chain consists of a manufacturer and a retailer who is responsible for the used-product collection. Specifically, we have considered three settings, that is, no channel leader, the manufacturer as the leader and the retailer as the leader. The steady equilibrium and the optimal control strategies are derived in different channel power structures utilizing the open-loop control strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In recent years, the presence of large retailers such as Wal-mart and Carrefour has increased the importance of the retailers in the supply chain and changed the channel power structure of the supply chain (Mi et al [50]). Additionally, with the prevalence of collectors and their leading roles, collector-led CLSCs are increasingly popular (Karakayali et al [51]).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the presence of large retailers such as Wal-mart and Carrefour has increased the importance of the retailers in the supply chain and changed the channel power structure of the supply chain (Mi et al [50]). Additionally, with the prevalence of collectors and their leading roles, collector-led CLSCs are increasingly popular (Karakayali et al [51]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They conclude that the centralized model outperforms the decentralized scenarios in terms of the system profit. Using the open-loop control strategy method, Jackson et al [50] explore the steady equilibrium and the optimal control strategies in three settings: no channel leader, the manufacturer as the leader and the retailer as the leader. By the numerical comparison of the profit rate of the supply chain members, they find that both manufacturer and retailer have an incentive to play the channel leader's role.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, other types of games are identified in the framework of the Stackelberg model. We can refer to [6,89,90], who worked to formulate CLSCs based on differential games. These games are solved by the Hamilton-Jacobi-Bellman equation method [91,92].…”
Section: Game-based Clscsmentioning
confidence: 99%
“…We found that almost three-quarters of the investigated CLSCs studied the models under the leadership of the manufacturers. Some works found a disadvantage by considering the manufacturer as a leader, such as the lowest return rate [90] or a higher retail price and a lower collection effort [121]. However, others showed advantages from the perspective of the remanufacturing process and consumers' welfare [58].…”
Section: Academic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation